Exploring Relationships Between Grit, Belonging, Institutional Compassion, Pandemic Stress, and Goal Progress Among Emerging Adult Post-Secondary Students. Issue 4 (August 2022) - Schmahl, Cynthia A. M.; Nguyen, Jacqueline
Grit and belonging are consistently important factors in emerging adult academic outcomes (Morrow & Ackermann, 2012). This study examines the role of grit (i.e., goal perseverance, consistency of interest, and adaptability), belonging (i.e., sense of fitting in and feeling valued), and perceived institutional compassion (i.e., care/support and resources for students in pandemic-related responses) in emerging adults' academic goal pursuits amid COVID-19 challenges. Emerging adult participants (age 18–24; N = 258) representing a diverse sample of traditional, full-time, undergraduate students across the United States (60% women; 47.31% White, 18.46% Black/African American, 17.31% Asian, 10.77% Hispanic/Latino/a/x), completed an online survey assessing pandemic-related stress, grit, belonging, goal pursuits, and the newly developed Institutional Compassion Scale (Schmahl, 2021). Unexpectedly, pandemic-related stress was unrelated to student assessments of their progress toward academic short- and long-term goals. But grit and belonging were associated with pandemic-related stress: high stress is associated with a weaker sense of belonging and with lower grit. Institutional compassion was associated with all three major study variables: grit, sense of belonging, and stress. Higher institutional compassion was associated with a greater sense of belonging and less pandemic-related stress. The importance of grit, belonging, and particularly institutional compassion are discussed as they pertain to emerging adults' perceptions of themselves as progressing toward their goals during stressful periods such as the onset of the COVID-19 pandemic.